Second International Consensus Conference on Advanced Breast Cancer (ABC2), Lisbon, 11/09/2013: the German Perspective - Harbeck, Nadia; Marschner, Norbert; Untch, Michael; Decker, Thomas; Hegewisch-Becker, Susanna; Jackisch, Christian; Huober, Jens; Lück, Hans-Joachim; Minckwitz, Gunter von; Scharl, Anton; Schneeweiss, Andreas; Tesch, Hans; et al. (Breast care, 2014)
Locally advanced breast cancer; LABC; Metastatic breast cancer; MBC; Consensus AGO